Limnological parameters and metals concentrations in water in three lagoons of the metropolitan region of Salvador, Bahia, Brazil - Silva, Ana Carina; Azevedo, Isabel Honorata Souza; Gonçalves, Manuel Vitor; Milazzo, Alexandre Dacorso Daltro; Cruz, Manoel Jerônimo; Nascimento, Sergio Augusto Morais (Pesquisas em Geociências, 2021)
This work aims to describe the seasonal variability of physicochemical and metal parameters in three lakes of the city of Salvador-BA (Pituaçú and Paixão lagoons and Tororó dike), between 2014 and 2017, with special emphasis on regarding classification and suitability for the use for amateur fishing, recreation, conservation, and landscape harmony. Physicochemical parameters were measured in situ and aliquots of water were collected for laboratory analysis at different seasonal periods from 2014 to 2017. Metal concentrations in water (Al, As, Ba, B, Cd, Ca, Cr, Co, Cu, Fe, Pb, Mg, Mn, Hg, Ni, K, Se, V, and Zn) were determined by ICP-OES. The pH ranged from 5.5-8.9 (7.5 ± 0,.7); water temperature, 22.0-33.20 (26.68 ± 2.11) °C; dissolved oxygen, 0.72-10.87 (6.31 ± 1.65) mg.L-1; turbidity, 0.43-188.0 (23.54 ± 31.86) NTU and conductivity, 0.19-2.60 (0.44 ± 0.35) mS.cm-1. Fe (all lagoons), Pb and Mn (Paixão and Pituaçú lagoons) and Al (Pituaçu lagoon) presented average values above the maximum limits stipulated by CONAMA evidencing the degradation of water quality. Water parameters were considered appropriate for its current use, although commonly the dissolved oxygen and turbidity values are not consistent with the standard stipulated in CONAMA Resolution 357/05 (> 5 mg.L-1 for dissolved oxygen and up to 100 NTU for turbidity). Attention should be drawn especially to the values obtained for dissolved metals (especially Fe, Pb, Mn, and Al), which have been shown to be at certain seasonal periods or at constant (Mn) levels dangerously above the stipulated limits. Due to the possibility of harmful effects, there is a need for intervention and protection in these areas, and continuous monitoring, aiming to improve water quality and respond to major uses.